Variation in Citational Practice in a Corpus of Student Biology Papers: From Parenthetical Plonking to Intertextual Storytelling. (January 2014) - Swales, John M.
This is a corpus-based study of a key aspect of academic writing in one discipline (biology) by final-year undergraduates and first-, second-, and third-year graduate students. The papers come from the Michigan Corpus of Upper-level Student Papers, a freely available electronic database. The principal aim of the study is to examine the extent of variation in citation practice in the biology subcorpus. To that end, it explores citation practices from a number of perspectives, including the distribution of integral versus parenthetical citations, the choice of reporting verbs, the effect of citing system, and the occurrence of selected features such as the use of citees' first names. Results show little difference between the undergraduate and graduate papers, some effect of the citing system, and a somewhat richer intertextuality in the "evolutionary" as opposed to the "molecular" biology papers. Overall, this is an impressive body of student work from the viewpoint of textual variation in citation practice, but it should be remembered that the corpus consists of only "A" papers from a flagship research university.